The universal right to health care - José Manuel Peixoto Caldas; Zélia Maria de Sousa Araújo Santos (Rev Rene)
Forty years ago, the 30th World Health Assembly was organized by the World Health Organization, whichled the movement “Health for everybody in 2000” resulting in the elaboration of a document entitled Declarationof Alma-Ata, reaffirming the meaning of health as a fundamental human right and one of the most importantglobal goals for social improvement.